Reliability Perception for Islamic Websites - Nassr, rasheed Mohammad; mahmud, murni (Journal of Computing Technologies and Creative Content, 2019)
Muslims use the internet as a medium to disseminate Islam. This is seen as necessary due to the wide distribution of Muslims globally and difficulties to establish Islamic centres to teach Muslims and perform dawah (delivering message). Along with this, whether Islamic online information can be trusted has been questioned. The increase in cases of finding unreliable and sometime Islamophobia content websites and questionable authenticity of online information has led researchers and organisations to respond to the reliability issues. This study explores the reliability perception in relation to Islamic websites from Muslim users’ perspective. The findings suggest that availability of Quranic verses, availability of citations for authentic prophetic biography, referencing authentic Hadith, reflecting mathahib perspectives, scholars’ and organisations’ involvement, and recommended websites’ content features are the major factors that influence the reliability of Islamic websites. Those factors cultivate the belief that Islamic websites have reliable, authentic, and wellreferenced content. Emphasising these factors would increase the perceived level of reliability of Islamic websites, which would increase the acceptance for the Islamic messages delivered.